Evaluating the Impact of EU Expenditures Under Agricultural Priorities on Energy Sustainability in CEE Countries - Nicoleta Mihaela Doran; Gabriela Badareu; Marius Dalian Doran; Mihai Alexandru Firu; Anamaria Liliana Staicu (Agriculture, 2025)
This study examines the impact of EU agricultural expenditures on renewable energy production and energy efficiency in the agricultural sector across nine Central and Eastern European (CEE) countries over the period 2015–2022. The analysis is based on a panel dataset compiled from European Commission databases, incorporating annual expenditures under five Common Agricultural Policy (CAP) priorities, as well as indicators of renewable energy production and direct energy consumption in agriculture and forestry. Using panel regression models, the study assesses how different CAP funding priorities influence energy sustainability outcomes. The findings indicate that certain funding priorities significantly contribute to renewable energy adoption, while others have a limited effect, emphasizing the need for a more targeted policy approach. The results also highlight regional disparities in the effectiveness of CAP funding, suggesting that farm structure, institutional capacity, and climate conditions mediate the impact of EU expenditures on energy sustainability. These insights contribute to the ongoing discourse on optimizing EU funding mechanisms to support a sustainable agricultural transition in the CEE region.